SMART CLASS INNOVATION USING TES DUGA TO ACCELERATE STUNTING PREVENTION IN AGRICULTURAL AREAS - Musviro; Hayati, Nurul; Rahmawati, Iis (Universitas Airlangga, 2025)
Breaking the chain of stunting by increasing parental understanding is necessary. This study aims to analyze the effectiveness of the Smart Class innovation using the 'Tes Duga' Snakes and Ladders game in improving parental knowledge to accelerate stunting prevention and reduction in agricultural areas. This study employed a pre-experimental one-group pre-test-post-test design. This study used a sample of 107 parents who have toddlers. Data collection was carried out using a questionnaire. The data obtained were analyzed using the Wilcoxon signed-rank test. The analysis indicated a statistically significant improvement in parental knowledge and attitudes, with a p-value of 0.000 (p < 0.05). These results show that the innovation of the Smart Class Program through the Guess Test game effectively increases parents' knowledge about preventing and reducing stunting. As an educational method, the Smart Class Program has the advantages of being interactive and fun for learning parents in agronursing areas, preventing stunting, and having an average increase in parental knowledge before the intervention of 73.36. After the intervention, the average increased significantly, namely 87.01. This innovative approach has the potential to be applied more widely as part of national efforts to overcome the problem of stunting in Indonesia.